2009
DOI: 10.1007/s11947-009-0206-y
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activities of Rapeseed Protein Hydrolysates

Abstract: Rapeseed protein hydrolysates (RPH) were obtained by enzymatic hydrolysis of rapeseed protein using Alcalase 2.4 L FG. The degree of hydrolysis (DH) of RPH was about 25% using pH-stat method. The antioxidant activities of RPH were investigated by employing several in vitro assay, including the 1,1-diphenyl-2-picrylhydrazyl (DPPH)/superoxide/hydroxyl radical scavenging assays, and reducing power assay. RPH showed scavenging activity against free radicals such as DPPH, superoxide, and hydroxyl radicals. The radi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
61
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(68 citation statements)
references
References 51 publications
(60 reference statements)
6
61
1
Order By: Relevance
“…Superoxide radicals were generated by pyrogallic acid method with some modification [12][13][14]. The reaction mixture contained 2 mL sample (0.0 -1 mg/mL) dis-solved in 2.25 mL Tris-HCl buffer (0.05 M, pH 8.0).…”
Section: Scavenging Activity Of Superoxide Radicalmentioning
confidence: 99%
See 1 more Smart Citation
“…Superoxide radicals were generated by pyrogallic acid method with some modification [12][13][14]. The reaction mixture contained 2 mL sample (0.0 -1 mg/mL) dis-solved in 2.25 mL Tris-HCl buffer (0.05 M, pH 8.0).…”
Section: Scavenging Activity Of Superoxide Radicalmentioning
confidence: 99%
“…The reducing power of extracts was determined according to the Method described before [11,13,15,16] with slight modification. A 1 mL of extract sample or standard antioxidant (ascorbic acid) was mixed with 2.5 mL of 0.2 M phosphate buffer saline (pH 6.6) and 2.5 mL of 1% (w/v) potassium ferricyanide [K 3 Fe(CN) 6 ].…”
Section: Determination Of Reducing Powermentioning
confidence: 99%
“…Extracts with higher electron donating activity can terminate the radical chain and turn free radicals into more stable products (Pan et al 2011). The extracts in the present study were shown to have considerable amounts of phenolic compounds that can donate electrons.…”
Section: Total Antioxidant Capacitymentioning
confidence: 53%
“…There was no significant difference in the reducing power between DH-10 and DH-20. However, the reducing power of GSH with DH of 5-20 % at 6 mg mL −1 was in the range of 0.77-1.17, which is higher than that of some plant protein hydrolysates (Li et al 2008;Pan et al 2011). The results showed that GSH is a good electron donor and inhibits free radicals, indicating that it has strong potential for use as a natural antioxidant.…”
Section: Reducing Powermentioning
confidence: 83%